2022
DOI: 10.1038/s41467-022-29121-x
|View full text |Cite
|
Sign up to set email alerts
|

Thermosensitive hydrogel releasing nitric oxide donor and anti-CTLA-4 micelles for anti-tumor immunotherapy

Abstract: Due to their autosynchronous roles in shaping the anti-tumor immune response, complex immune regulatory networks acting both locally within the tumor microenvironment as well as in its draining lymph nodes play critical roles in the cancer immunotherapy response. We describe herein a thermosensitive co-polymer hydrogel system formed from biocompatible polymers gelatin and Pluronic® F127 that are widely used in humans to enable the sustained release of a nitric oxide donor and antibody blocking immune checkpoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(64 citation statements)
references
References 50 publications
1
63
0
Order By: Relevance
“…The ICG exposed with laser group showed unevenly tumor sizes which possibly caused by the individual differences of mice. Mice are biologically independent samples, they have inconsistent logarithmic tumor growth cycles [55 , 56] . For this reason, we set 6 mice per group to avoid the possible individual differences.…”
Section: Resultsmentioning
confidence: 99%
“…The ICG exposed with laser group showed unevenly tumor sizes which possibly caused by the individual differences of mice. Mice are biologically independent samples, they have inconsistent logarithmic tumor growth cycles [55 , 56] . For this reason, we set 6 mice per group to avoid the possible individual differences.…”
Section: Resultsmentioning
confidence: 99%
“…Still, its function is inhibited by the expansion of other immune cells expressing CTLA-4. Thomas et al (130) synthesized a thermosensitive hydrogel F127-g-using Pluronic ® F127 and gelatin by a simple chemical coupling Gelatin hydrogel loaded with NO donor GSNO and CTLA-4 antibody. The results showed that the F127-g-gelatin hydrogel combined with GSNO and CTLA-4 antibody had more substantial anti-tumor effects on tumor-bearing mice than saline, bare hydrogel and free GSNO + CTLA-4 antibody.…”
Section: Local Injection Of Hydrogelmentioning
confidence: 99%
“…The cumulative NO release is calculated to be 2.48×10 -4 and 2.36×10 -4 moles, respectively, confirming that the presence of αCD does not consume NO. NO-releasing hydrogels have been shown to promote wound healing in topical applications [55], enhance tumor immunotherapy as injectables [56], and protect medical implants as coatings [8].…”
Section: Effect Of Cds On the Thermal Decomposition Of Gsno In Aqueou...mentioning
confidence: 99%